Ukraine : Report on the Observance of Standards and Codes - Data Module; Response by the Authorities; and Detailed Assessments Using the Data Quality Assessment Framework. - International Monetary Fund. (Washington, D.C. : International Monetary Fund, 2003)
The data dissemination module of the Report on the Observance of Standards and Codes (ROSC) provides an in-depth review of Ukraine's statistical system. The report provides an assessment of Ukraine's data dissemination practices in relation to the IMF's Special Data Dissemination Standard (SDDS), and the quality of the data disseminated using the Data Quality Assessment Framework (DQAF) developed by the IMF's Statistics Department. It also assesses data quality for the national accounts, consumer and producer prices, government finance, monetary, and balance-of-payments statistics.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet